The Contribution of Social Studies Education in Shaping Students' Environmental Awareness at SMP Negeri 4 Parepare: A Case Study of an Adiwiyata Awardee School - Yulanda Yulanda; Nurleli Ramli; Bahtiar Bahtiar; Nasruddin Nasruddin (STKIP Taman Siswa Bima, 2025)
The issue of environmental degradation, such as pollution, deforestation, and inefficient waste management, requires serious attention in efforts to cultivate ecological awareness from an early age. This study aims to examine the contribution of Social Studies (IPS) education in shaping students' environmental awareness at SMP Negeri 4 Parepare, a recipient of the Adiwiyata award. The environment-based learning implemented at this school integrates environmental issues with practical activities, such as reforestation and waste management, to enhance students' ecological awareness. The research employed a qualitative descriptive approach with a case study design, involving observations, interviews with students, teachers, and the school principal, as well as documentation of learning activities focused on environmental principles. The findings indicate that IPS education at SMP Negeri 4 Parepare successfully instills environmental care attitudes among students. Practical activities involving students in real-life actions, such as tree planting and cleanliness campaigns, strengthen their understanding of the importance of preserving nature. Furthermore, the role of teachers as facilitators and role models in applying Adiwiyata-based education significantly supports the success of this learning approach. Therefore, the study concludes that integrating environment-based IPS education can shape students' environmentally responsible characters and can serve as a reference for other schools in developing effective environmental education.